Pengembangan Desa Wisata Berbasis Collaborative Governance Di Desa Blahbatuh Kabupaten Gianyar - Prabawati, Ni Putu Anik; Supriliyani, Ni Wayan (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p21, 2023)
One of Gianyar Regency's tourist settlements is Blahbatuh Village. In Blahbatuh Village, Blahbatuh District, Gianyar Regency, this study aims to ascertain the type of collaborative governance in tourism village development. All parties, including the government, society, and other stakeholders, are hoped to benefit from collaborative governance. Descriptive qualitative research methodology was employed in this study. The analysis makes use of collaboration success measures developed by Deseve and collaboration process indicators developed by Ansell and Gash. The findings of this study demonstrate that the Blahbatuh Village administration has established partnerships with several groups, including the commercial sector and the local community, to build the Blahbatuh Tourism Village and boost the local tourism industry and economy. The findings of this study demonstrate that the government of Blahbatuh Village has established partnerships with several groups, including the private sector and the local population, to build the Blahbatuh Tourism Village and boost the local community's economy and tourism. The establishment of the Blahbatuh Tourism Board (BTB), a community-based management organization for the tourism village, is one example of teamwork. The researcher's conclusion is that the Blahbatuh Village Government's Collaboration process, while in line with Deserve's Collaboration success metrics, is nevertheless hindered by the availability of human resources. This study makes the recommendation to increase the actors' level of trust in the program and its objectives. This study makes the recommendation to increase the players' level of trust in the program and its objectives while also forging cooperative linkages in the form of rules. Keywords: Collaborative, Governance, Tourist Village